MENINGKATKAN PEMAHAMAN KONSEP BANGUN DATAR MENGGUNAKAN MEDIA FLASHCARD STEM LIDI PADA SISWA KELAS V SD - Pohan, Elviza Nabilla; Rahman, Arief Aulia; Irvan, Irvan; Hasibuan, Anggi Tri Dhani (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This Classroom Action Research (CAR) aimed to improve the understanding of plane figure concepts among fifth-grade students at SDN 066054 Medan through the use of STEM Stick Flashcard media. The research was conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection, using a Culturally Relevant Teaching (CRT) approach. In the pre-cycle stage, learning was conducted conventionally, and only 40% of students achieved the Minimum Mastery Criteria (KKM). After improvements through discussion-based approaches in Cycle I, the mastery level increased to 60%. In Cycle II, learning incorporated STEM Stick Flashcards that combined visual representations of plane figures and traditional Ulos cloth motifs. The results showed that 90% of students reached mastery and demonstrated increased participation, confidence, and more meaningful conceptual understanding. Thus, the STEM Stick Flashcard media proved to be effective in enhancing students’ understanding of plane figures while creating a fun and contextual learning environment.